If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2(4 + -3x) = 114 2x + (4 * 2 + -3x * 2) = 114 2x + (8 + -6x) = 114 Reorder the terms: 8 + 2x + -6x = 114 Combine like terms: 2x + -6x = -4x 8 + -4x = 114 Solving 8 + -4x = 114 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -4x = 114 + -8 Combine like terms: 8 + -8 = 0 0 + -4x = 114 + -8 -4x = 114 + -8 Combine like terms: 114 + -8 = 106 -4x = 106 Divide each side by '-4'. x = -26.5 Simplifying x = -26.5
| 3(x^2-1)=0 | | -5(4x-2)=-2(6x+3) | | 2*cos^2x=sinx | | Ln(x-4)=ln(x+6)-lnx | | 2x-3+(4x-10)=180 | | t^2+t+56=0 | | (4t+2)(5t-7)=0 | | 0.5x-0.23=5.77 | | (5y+2)-1=(1-2y) | | -2+11=4y-7y | | x^4-6ax^3+9a^2x^2-1= | | 60+0.50r=1.30r | | 4v=3v-8 | | x+3=6x+2 | | -36.838+10m=-2.3(-5.6m+6.5) | | 2y+72=180 | | (3p-2)(p+9)=0 | | h+9.5=-9.7 | | 25x^3+15x^2+2x=0 | | 3x+2(5x+4)=43 | | 7e^5x+8=0.23 | | 8x^2(2x+9)+(2x+9)=0 | | a/10-8=24 | | 5x+2x-3=17 | | 28-2c=6c+4 | | 12x^2-x=16x+40 | | 2p^2+6p+3=0 | | 180=(6x-19)+(3x+32) | | -4r^2+3+r=0 | | 2w+17=21+3w | | 12n+25=-35 | | 6r+4=5r-8 |